Survival analysis of the randomised phase III GeparOcto trial comparing neoadjuvant chemotherapy of intense dose-dense epirubicin, paclitaxel, cyclophosphamide versus weekly paclitaxel, liposomal doxorubicin (plus carboplatin in triple-negative breast cancer) for patients with high-risk early breast cancer. (January 2022) - Schneeweiss, Andreas; Michel, Laura L.; Möbus, Volker; Tesch, Hans; Klare, Peter; Hahnen, Eric; Denkert, Carsten; Kast, Karin; Pohl-Rescigno, Esther; Hanusch, Claus; Link, Theresa; Untch, Michael; et al.
Abstract: Background: GeparOcto demonstrated that pathological complete response (pCR) of intense dose-dense epirubicin, paclitaxel and cyclophosphamide (iddEPC) was comparable to weekly paclitaxel/non-pegylated liposomal doxorubicin (plus carboplatin (PM(Cb) in triple-negative breast cancer [TNBC]) in high-risk early breast cancer (BC). Here, we report time-to-event secondary end-points. Patients and methods: Patients were randomised to receive 18 weeks of E (150 mg/m 2 ) followed by P (225 mg/m 2 ) followed by C (2000 mg/m 2 ), each q2w or weekly P (80 mg/m 2 ) plus M (20 mg/m 2 ) plus, in TNBC, Cb (AUC 1.5). Patients with human epidermal growth factor receptor 2-positive (HER2+)BC received trastuzumab (6[loading dose 8]mg/kg q3w) and pertuzumab (420[840]mg q3w) with P and C cycles. Results: 945 patients started treatment (iddEPC n = 470; PM(Cb) n = 475). After a median follow-up of 47.0 (range 1.6–61.5) months, 162 (75 in iddEPC; 87 in PM(Cb)) invasive disease-free survival (iDFS) events and 79 (41 in iddEPC; 38 in PM(Cb)) deaths were reported. No significant difference was observed in 4-year iDFS (81.9% iddEPC versus 79.7% PM(Cb), HR = 1.16 [95%CI 0.85–1.59], log-rank p = 0.334) or 4-year overall survival (OS) (90.3% iddEPC versus 90.6% PM(Cb), HR = 0.90 [95%CI 0.58–1.40], log-rank p = 0.637) overall and in HER2+ and TNBC subgroups. HR+/HER2- BC patients, however, had significantly better 4-year iDFS (77.9% iddEPC versus 62.5% PM, HR = 2.11 [95%CI 1.08–4.10], log-rank p = 0.025) and 4-year OS with iddEPC (94.7% iddEPC versus 80.1% PM, HR = 3.26 [95%CI 1.06–10.00], log-rank p = 0.029). Conclusion: While there was no difference in survival for the entire cohort, the HR+/HER2-subgroup significantly benefits from iddEPC. This supports the concept of an additional effect of NACT beyond pCR in patients with HR+/HER2- BC. ClinicalTrials.gov identifier: NCT02125344 . Highlights: No significant survival difference for the entire cohort, HER2+ and TNBC subgroups. Patients with HR+/HER2-patients benefit from iddEPC despite no difference in pCR rate. Effect of neoadjuvant chemotherapy beyond pCR in the HR+/HER2- subgroup.